Pregled zbiranja in urejanja metapodatkov pri sistemu za upravljanje biotehniške zbirke WebAgris - Bartol, Tomaž (Knjižnica, 2008)
The paper tackles international information system for agriculture Agris and local processing of metadata with database management software WebAgris. Operations are coordinated by the central repository at the FAO in Rome. Based on international standards and unified methodology, national and regional centers collect and process local publications, and then send the records to the central unit, which enables global website accessibility of the data. Earlier DOS-run application was based on package Agrin CDS/ISIS. The Current package WebAgris runs on web servers. Database construction tools and instructions are accessible on FAO Web pages. Data are entered through unified input masks. International consistency is achieved through authority control of certain elements, such as author or corporate affiliation. Central authority control is made available for subject headings, such as descriptors and subject categories. Subject indexing is based on controlled multilingual thesaurus Agrovoc, also available freely on the Internet. This glossary has become an important tool in the area of the international agricultural ontology. The data are exported to the central unit in XML format. Global database is currently eccessible to everyone. This international cooperative information network combines elements of a document repository, electronic publishing, open archiving and full text open access. Links with Google Scholar provide a good possibility for international promotion of publishing.
Keywords: informacijski sistemi; podatkovne zbirke; mednarodno sodelovanje; kmetijstvo; agriculture; dokumenti; metapodatki; predmetne oznake; tezavri